Optical Technologies for Telecommunications 2012 2013
DOI: 10.1117/12.2021007
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of predictive control strategy for maintenance of fiber optic communication lines

Abstract: The paper considers the implementation of innovative strategy of predictive parameter control of outside plant communication (OPC) for maintenance of fiber optic communication lines (FOCL). The choice of a predictive control method is reasonable. Realization of this technology for estimation the maintenance effectiveness of OPC FOCL by criterion of reliability is shown on the example of calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
3
0
Order By: Relevance
“…If to assume that one full-year cycle it conditionally two seasons -a season positive and a season of negative temperatures which are characterized by some average value of stress in optical fiber, then from (2) follows a formula: 4. The analysis showed that in the calculation of the optical cable lifetime is sufficient to consider only the first stage fiber failure [13][14][15][16][17][18][19][20][21] . Then, formula (3) and the condition of failure fibers: …”
Section: Optical Cable Lifetimementioning
confidence: 99%
See 1 more Smart Citation
“…If to assume that one full-year cycle it conditionally two seasons -a season positive and a season of negative temperatures which are characterized by some average value of stress in optical fiber, then from (2) follows a formula: 4. The analysis showed that in the calculation of the optical cable lifetime is sufficient to consider only the first stage fiber failure [13][14][15][16][17][18][19][20][21] . Then, formula (3) and the condition of failure fibers: …”
Section: Optical Cable Lifetimementioning
confidence: 99%
“…The lifetime of the optical fibers is determined by stress corrosion process and depends from the mechanical stress in the optical fiber [1][2][3][4][5][6][7] . Researches of deformations of optical cables at the low temperatures showed that residual radial deformations of optical cables loose tubes can be the cause [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Such deformations can be the cause of optical fibers stress at low negative temperatures and the cause of optical cables reliability decrease at fiber optical communication lines maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the increase in attenuation in optical fibers modular cables at low temperatures due to the decrease of negative bending radii of the fibers in the modular tubes [1,[10][11][12][13]. Accordingly, for the prediction of changes in the damping of optical fibers must evaluate changes radii fibers and calculate the bending loss.…”
Section: Introductionmentioning
confidence: 99%